Metagenomic Sequencing Analysis and Microbial Identification on Various Landcover - Rossyda Priyadarshini; Elly Syafriani; Medina Uli Alba Somala; Amir Hamzah (Nusantara Science and Technology Proceedings)
Soil degradation will affect the availability of soil nutrients. Microbes role was important in supplying soil nutrient. How is microbes supply the nutrients can be learned through the metagenome technique. Metagenome is one of the molecular techniques that can identify microbial communities from soil samples that are used quickly and precisely. Through the metagenome technique, not only information about the identity of microbial species can be obtained, but also the enzymes produced, which will affect the soil nutrients availability. This study aims to detect and identify the impact of land cover types on microbial types. Soil samples were taken under agricultural land (LP) and agroforestry (AF). Each type of land cover was taken at 4 (four) different locations. The method used in this research is a molecular-based species identification method through metagenome analysis. This study showed that there are variations in microbial species in various types of land cover. This information is important for sustainable agricultural management in the future. Our study showed that on all of the land cover types, Proteobacteria were the most abundant phylum in all of the land cover patterns. Among them, s_Sphingomonas_melonis; f_Sphingomonadaceae; g_Sphingomonas; c_Alphaproteobacteria; p_Proteobacteria; and o_Sphingomonadales were the most abundant in the LP groups, while p_Acidobacteria and c_Deltaproteobacteria were the most abundant in AF groups. This composition of soil metagenomic was associated with the soil physic-chemical properties, especially pH and soil organic matter.